Use of SEM/EDX methods for the analysis of ambient particulate matter adhering to the skin surface - Mirakovski, Dejan; Damevska, Katerina; Simeonovski, Viktor; Nikolovska, S; Boev, Blazho; Petrov, Andrej; Sijakova Ivanova, Tena; Zendelska, Afrodita; Hadzi-Nikolova, Marija; Boev, Ivan; Dimov, Gjorgji; Darlenski, Razvigor; et al. (Wiley, 2022)
The skin is exposed to numerous particulate and gaseous air pollutants. The ones that need particular attention are the particles that adhere to the skin surface, which can later cause direct skin damage. This study aimed to characterize air pollution (AP) particles adhered to the human skin by using scanning electron microscopy (SEM) combined with X-ray dispersive energy spectrometry (EDX).